Neuronal Fat and Dendrite Morphogenesis: The Goldilocks Effect. Issue 5 (May 2018) - Sundararajan, Lakshmi; Miller, David M.
Abstract : Two recent studies by Meltzer et al. and Ziegler et al. use Drosophila larvae to demonstrate that cell-autonomous regulation of lipid biosynthesis defines the complexity and function of highly branched nociceptive neurons. Their findings show that lipid biosynthesis in the neuron is fine-tuned for optimal dendrite morphology and sensitivity.